2021
DOI: 10.4103/ijo.ijo_308_21
|View full text |Cite
|
Sign up to set email alerts
|

iStent versus iStent inject implantation combined with phacoemulsification in open angle glaucoma

Abstract: Purpose: To compare the outcomes of iStent vs. iStent inject implantation combined with phacoemulsification. Methods: This single center retrospective comparative case series included subjects with open angle glaucoma who underwent iStent or iStent inject implantation combined with phacoemulsification with ≥1 year follow-up. The main outcome measures were in-group and between-group changes in intraocular pressure (IOP) and medication number, proportion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 38 publications
4
20
1
1
Order By: Relevance
“…35,36 Shalaby et al found that compared with eyes undergoing phaco/iStent with the first-generation device, phaco/iStent inject eyes exhibited greater IOP reduction (14.9 ± 3.6 vs. 15.1 ± 3.5 mm Hg, P = 0.003) and a higher proportion achieving postoperative IOP < 15 mm Hg (70.7% vs. 49.2%, P = 0.003). 37 Similar results were observed by Guedes et al in a longitudinal retrospective study including 73 eyes (38 eyes phaco/iStent first generation, 35 phaco/iStent inject). After 6 months, phaco/iStent inject eyes demonstrated a significantly greater IOP reduction (26.6% vs. 15.8%, P = 0.005), with a higher percentage of iStent inject eyes achieving IOP < 18 mm Hg (100% vs. 86.8%).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…35,36 Shalaby et al found that compared with eyes undergoing phaco/iStent with the first-generation device, phaco/iStent inject eyes exhibited greater IOP reduction (14.9 ± 3.6 vs. 15.1 ± 3.5 mm Hg, P = 0.003) and a higher proportion achieving postoperative IOP < 15 mm Hg (70.7% vs. 49.2%, P = 0.003). 37 Similar results were observed by Guedes et al in a longitudinal retrospective study including 73 eyes (38 eyes phaco/iStent first generation, 35 phaco/iStent inject). After 6 months, phaco/iStent inject eyes demonstrated a significantly greater IOP reduction (26.6% vs. 15.8%, P = 0.005), with a higher percentage of iStent inject eyes achieving IOP < 18 mm Hg (100% vs. 86.8%).…”
Section: Introductionsupporting
confidence: 83%
“…The iStent inject has shown greater efficacy compared with the first-generation iStent 35,36 . Shalaby et al found that compared with eyes undergoing phaco/iStent with the first-generation device, phaco/iStent inject eyes exhibited greater IOP reduction (14.9 ± 3.6 vs. 15.1 ± 3.5 mm Hg, P = 0.003) and a higher proportion achieving postoperative IOP < 15 mm Hg (70.7% vs. 49.2%, P = 0.003) 37 . Similar results were observed by Guedes et al in a longitudinal retrospective study including 73 eyes (38 eyes phaco/iStent first generation, 35 phaco/iStent inject).…”
Section: Non-bleb Forming Trabecular Meshwork Canal Implantsmentioning
confidence: 99%
“…In a study of 197 eyes with mild to severe open-angle glaucoma, Shalaby et al observed that eyes implanted with the iStent inject achieved lower IOPs at month 6 (−14% vs −8%), with comparable surgical success (>20% IOP reduction from baseline) seen in both groups at 6 and 12 months after surgery. 24 Both groups experienced significant medication reductions (−35% vs −18%) and improvement in visual field mean deviation at 12 months. 24 Guedes et al compared outcomes in 58 eyes with primarily (96.6%) mild-to-moderate open-angle glaucoma and observed greater efficacy in the iStent inject group, with a significantly higher percentage of iStent inject eyes achieving an IOP <18 mmHg (100% vs 80%) and <15 mmHg (73.9% vs 34.3%) at 12 months.…”
Section: Istent Vs Istent Injectmentioning
confidence: 86%
“… 24 Both groups experienced significant medication reductions (−35% vs −18%) and improvement in visual field mean deviation at 12 months. 24 Guedes et al compared outcomes in 58 eyes with primarily (96.6%) mild-to-moderate open-angle glaucoma and observed greater efficacy in the iStent inject group, with a significantly higher percentage of iStent inject eyes achieving an IOP <18 mmHg (100% vs 80%) and <15 mmHg (73.9% vs 34.3%) at 12 months. 25 Mean medication numbers were also significantly lower in the iStent inject group (0.1 vs 0.5 medications).…”
Section: Istent Vs Istent Injectmentioning
confidence: 86%
“…Diese Ergebnisse wurden von Manning auch in einem Vergleich 12 Monate nach der Implantation bestätigt [14]. Shalaby et al stellten nach 12 Monaten keinen signifikanten Unterschied in der IOD-Senkung fest, aber die benötigten topischen Antiglaukomatosa konnten nach iStents inject-Implantation stärker reduziert werden als nach Implantation von iStents der ersten Generation [15].…”
Section: üBersicht üBer Die Einzelnen Operationsverfahrenunclassified